ANALYSIS OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) ON EXCAVATOR HITACHI EX2500-6 - Agus Daman; Dewi Nusraningrum (Dinasti International Journal of Education Management And Social Science, 2020)
The Mining Industry is one of the pillars of national economic development. In this industry, heavy equipment plays an important role in the coal mining process in Indonesia. By using heavy equipment must be well structured, so that the project can run easily without any obstacles. This research aimed to evaluate the cause of the low-value OEE of the Excavator Hitachi EX2500-6 of EX157 and EX158 units and determine the way to repair so that the equipment performance can be improved. This research uses descriptive quantitative approach with value analysis methods Overall Equipment Effectiveness (OEE). The result of OEE values were analyzed using losses classification method so that the occurrence of loss factors can be found and root cause analysis performance using a causal diagram/fishbone diagram and then make any improvement recommendations that can be done by using 5W1H analysis. Based on the research results, the OEE values of two excavators were calculated and were compared with the benchmark values. The values of OEE were found to be 84% for EX157 units and 68% for EX158 units. The low value of OEE on EX158 caused by unscheduled maintenance time losses amounting to 1188.3 hours. The high of time loss is influenced by trouble on Machine Frame, Structure, Body, and Cab components amounted to 60.9%. The root causes of the losses derived from the availability of external mechanics, the competence of mechanics, the availability of spare parts, and the implementation of condition monitoring was not optimal. While remedial steps can be taken by giving technical training program for mechanics as maintenance practice methodology.